The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1442-2050.2011.01295.x
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal tolerance to high-dose stereotactic ablative radiotherapy

Abstract: Dose-volume parameters are needed to guide the safe administration of stereotactic ablative radiotherapy (SABR). We report on esophageal tolerance to high-dose hypofractionated radiation in patients treated with SABR. Thirty-one patients with spine or lung tumors received single- or multiple-fraction SABR to targets less than 1 cm from the esophagus. End points evaluated include D(5cc) (minimum dose in Gy to 5 cm(3) of the esophagus receiving the highest dose), D(2cc) , D(1cc) , and D(max) (maximum dose to 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…[23] This was a smaller series and included patients receiving SBRT as a boost to conventionally fractionated therapy, and the authors only analyzed a limited number of predetermined D v endpoints. Another series of central lung SBRT included a subset of 15 patients with tumors near the esophagus treated with 6 fractions of 8Gy and observed an overall 11% rate of acute Grade 1–2 esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…[23] This was a smaller series and included patients receiving SBRT as a boost to conventionally fractionated therapy, and the authors only analyzed a limited number of predetermined D v endpoints. Another series of central lung SBRT included a subset of 15 patients with tumors near the esophagus treated with 6 fractions of 8Gy and observed an overall 11% rate of acute Grade 1–2 esophagitis.…”
Section: Discussionmentioning
confidence: 99%
“…4,6,7 Stephans et al 5 demonstrated a late gradeZ3 incidence of 3.8%; however, both events were tracheoesophageal fistulas in patients given adjuvant VEGF-modulating agents. Abelson et al 16 reported a gradeZ4 toxicity rate of 6.4%. In our analysis, we demonstrated gradeZ2 and gradeZ3 esophagitis rates of 5.7% and 0.6%, respectively-in light of the few gradeZ3 events, it is therefore important to note that our dosimetric parameters are most predictive of the less severe grade 2 toxicities.…”
Section: Discussionmentioning
confidence: 98%
“…In an analysis of 182 patients treated with single-fraction SRS, Cox et al 7 revealed that D2.5 mL was the best predictor of esophagitis (P < 0.0006). In a cohort of 31 patients (treated with a wide variety of SBRT fractionation schemes), Abelson et al 16 studied the equivalent single-fraction BED3 to 1.0, 2.0, 5.0 mL, and maximal point and determined that severe toxicities occurred near previously published thresholds. Other studies have recommended the use of V15 in single-fraction SRS to prevent esophagitis.…”
Section: Discussionmentioning
confidence: 98%
“…Comparing to spinal cord, the dose constraints to the esophagus in spinal SRS/SBRT are less understood. Even though the dose constraint standard has yet been established for esophagus, partial volume constraints, such as dose to a small volume of 1 to 5 cc (D1 cc to D5 cc), and Dmax have been suggested in previous reports and used in clinical trials 18, 19, 20. Unlike a point dose, such as Dmax to the cord, which is unlikely to be effected by the extra vertebrae, a partial volume parameter, like D1 cc, generally increases with move critical structure volume receiving dose.…”
Section: Discussionmentioning
confidence: 99%